2023
DOI: 10.2147/prbm.s413738
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates’ Negative Emotion and Academic Procrastination During COVID-19: Life Autonomy as a Mediator and Sense of School Belonging as a Moderator

Xianpeng Tian,
Xiangwei Liu,
Zhiqi Xiao
et al.

Abstract: This study aims to investigate the impact of COVID-19 on undergraduate students' academic procrastination and negative emotions. It seeks to examine the relationship between negative affect and academic procrastination among university students, considering the mediating role of life autonomy and the moderating effect of a sense of school belonging. Methods:The study sample consisted of 776 university students from the Guangxi Zhuang Autonomous Region, China. Data collection involved the use of the Negative Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In our case, we can observe that the participating students in these focus groups are still adapting to the university environment, which, under this context, presents significant socialization challenges because they were abruptly removed from a high school environment, and this causes a lack of belonging to the university, because they entered amid the pandemic, and they did not have socialization among peers and professors, part of this is described by Xianpeng in (Xianpeng, et al, 2023).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In our case, we can observe that the participating students in these focus groups are still adapting to the university environment, which, under this context, presents significant socialization challenges because they were abruptly removed from a high school environment, and this causes a lack of belonging to the university, because they entered amid the pandemic, and they did not have socialization among peers and professors, part of this is described by Xianpeng in (Xianpeng, et al, 2023).…”
Section: Discussionmentioning
confidence: 84%
“…The pandemic was an unprecedented global event that caused negative impacts on the emotions of students. Anxiety, depression, stress, and fear are among the most documented negative emotions in various research studies, additionally, these studies also report mental health issues, psychological problems, a feeling of not belonging to the school, this has caused severe academic procrastination among students (Wang, 2022;(Xianpeng, et al, 2023). Steel defines procrastination as the voluntary delay of a planned course of action, despite expecting to be worse off due to the delay (Steel, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, numerous studies have suggested that selfdiscipline can bolster performance in tasks that require self-control and is linked to a range of positive outcomes, including academic success, decreased procrastination, and delayed gratification (Duckworth and Seligman, 2005;Waschull, 2005;Duckworth and Seligman, 2006;Shi and Qu, 2022). Secondly, a substantial amount of research indicates that self-efficacy and a sense of control, both closely related to a sense of successful self-discipline, can effectively reduce procrastination (Klassen et al, 2008;Katz et al, 2014;Wäschle et al, 2014;Zhang L. et al, 2018;Zhang Y. et al, 2018;Shao et al, 2023;Tian et al, 2023). Thirdly, heightened feelings of self-discipline can strengthen domains of behavioral self-control, such as promoting healthy eating behavior and pro-social decision-making (Tian et al, 2018).…”
Section: Introductionmentioning
confidence: 99%